Professional responsibility of notaries: ontological aspect - Вдовічена, Лідія; Вдовічен, Віталій (European Journal Of Law And Public Administration, 2019)
The problem of professional responsibility of the notary is related to the specifics of the performance by the notary of their professional duties. However, the fact of realization of the received powers as a consequence of the profession creates conditions for imposing on such a person the specific nature of responsibility. It (responsibility) is determined by the increased requirements for the profession of notary, in particular, to commit them all kinds of notarial acts. The disclosure of the ontological nature of the professional responsibility of the notary is associated with the following main aspects. First, the professional responsibility of the notary is complex, since it acts as a system legal category, and therefore has a whole set of specific features. Secondly, another problem is the professional responsibility of the notary – this is the distinction of responsibility of legal entities and individuals engaged in notarial activities, and in particular, a very specific attitude of the legislator to the category of «professional». Thirdly, this is a comparison of categories of professional duty and professional responsibility, and here the essential stimulus in the notarial activity is the correspondence of professional duty to personal convictions, interests and abilities of the notary. Fourthly, this distinction between the categories of legal and professional liability of the notary, in particular the problem of legal liability of the notary for the current reform of the notary in Ukraine, requires legislative regulation, in addition, the legislative uncertainty of the notary's liability institution testifies to the lack of guarantees of notarial activity.
Keywords: Responsibility; professional responsibility; notary public; professional responsibility of the notary; professional duty of the notary